1985
DOI: 10.1507/endocrj1954.32.265
|View full text |Cite
|
Sign up to set email alerts
|

Low serum levels of FSH, LH and prolactin in luteal phase inadequacy.

Abstract: In order to elucidate the relationship between prolaction (PRL) levels and corpus lutcum function in humans, assessment of temporal relationship between levels of PRL, LH, FSH, estradiol and progesterone was made in eleven normal cycling women and six short luteal women . All hormones were determined by specific radioimmunoassay.The mean PRL level in the luteal phase was higher than that in the follicular phase in normal women . On the other hand, no difference mean was seen between the PRL levels of follicula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1985
1985
1990
1990

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…However, it has been suggested that a reduction in FSH concentrations during the early follicular phase with crude inhibin could influence luteal function, resulting in luteal phase defects (Stouffer & Hodgen, 1980;diZerega & Hodgen, 1981;Jayaraman et ai, 1986). Minakami et al (1985) have attempted to correlate luteal phase defects with low serum FSH, LH and prolactin values in women and Wilks et ai (1976) observed that inappropriate FSH:LH ratios are responsible for short luteal phases seen in monkeys. Thau et ai (1979) reported that adult cyclic rhesus monkeys actively immunized against the ß subunit of ovine LH show normal follicular maturation, ovulation and corpus luteum formation but exhibit a luteal defect in that the corpus luteum is unable to support the establish¬ ment of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been suggested that a reduction in FSH concentrations during the early follicular phase with crude inhibin could influence luteal function, resulting in luteal phase defects (Stouffer & Hodgen, 1980;diZerega & Hodgen, 1981;Jayaraman et ai, 1986). Minakami et al (1985) have attempted to correlate luteal phase defects with low serum FSH, LH and prolactin values in women and Wilks et ai (1976) observed that inappropriate FSH:LH ratios are responsible for short luteal phases seen in monkeys. Thau et ai (1979) reported that adult cyclic rhesus monkeys actively immunized against the ß subunit of ovine LH show normal follicular maturation, ovulation and corpus luteum formation but exhibit a luteal defect in that the corpus luteum is unable to support the establish¬ ment of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators have failed to observe any systemic fluctuation on prolactin levels during the cycle (Ehara et al, 1973, McNeilly and Chard 1974, Epstein et al, 1975, while recent reports, referred to an overall pattern of serum prolactin during the menstrual cycle which resembled that for circulating estradiol (Franchimont et al, 1976, Vekemans et al, 1977, Djursing et al, 1981, Minakami et al, 1985 with small differences between the prolactin levels in the follicular and luteal phases.…”
mentioning
confidence: 99%